Stock and foreign exchange market linkages in emerging economies - Andreou, Elena; Matsi, Maria; Savvides, Andreas (My University, 2013)
This paper investigates bi-directional linkages between the stock and foreign exchange markets of a number of emerging economies. This is accomplished by estimating a vector autoregressive model with Generalized Autoregressive Conditional Heteroskedasticity (VAR-GARCH) for each of twelve emerging economies. Included in model dynamics are the effects of global and regional stock markets on the stock and foreign exchange markets. We find significant bi-directional spillovers between stock and foreign exchange markets. Moreover, we investigate whether a country's choice of exchange rate regime or the Asian financial crisis had a significant effect on the volatility spillover mechanism.
Keywords: Emerging economies; MGARCH; Volatility spillovers